2018
DOI: 10.1186/s12991-018-0214-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of global research output on diabetes depression and suicide

Abstract: BackgroundDiabetic patients, during the course of the disease, are most likely to experience depressive symptoms that might ultimately lead to suicidal ideation or suicide. The size of literature in diabetes depression/suicide is a good indicator of national and international efforts to address psychological co-morbidities associated with diabetes mellitus (DM). Therefore, the objective of this study was to give a comprehensive analysis, both quantitative and qualitative, of scientific literature in diabetes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…In 2016, a global report showed that among the 425 million people living with diabetes, approximately 80% of them resided in LMICs, and this figure is expected to increase significantly in the coming decades [1]. This disparity was in line with a previous bibliometric study about diabetes, depression, and suicide, though these same countries had the highest volume of publications on this topic [23]. Other scientometric studies also underlined the insufficient contribution of LMICs to research, which does not help diminish the diabetes burden in these nations [19,20,47,48].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In 2016, a global report showed that among the 425 million people living with diabetes, approximately 80% of them resided in LMICs, and this figure is expected to increase significantly in the coming decades [1]. This disparity was in line with a previous bibliometric study about diabetes, depression, and suicide, though these same countries had the highest volume of publications on this topic [23]. Other scientometric studies also underlined the insufficient contribution of LMICs to research, which does not help diminish the diabetes burden in these nations [19,20,47,48].…”
Section: Discussionmentioning
confidence: 59%
“…However, few publications feature updated quantitative data (i.e, bibliometric or scientometric analysis) focusing on interventions aimed at improving QOL in people living with diabetes. Recently, most of the published bibliometric studies have concentrated on diabetes in general [19][20][21], diabetic complications [22] or comorbidities [23], and the use of specific therapy in diabetes treatment [24]. Looking at these offers a comprehensive picture of the current approaches utilized for improving QOL, the status of international collaboration, and the gap between high-and low-income nations, which is vital in developing a roadmap for a global research agenda that will help optimize diabetes treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The current study showed that the mean number of citations per article and the h -index of the retrieved documents were low when compared to other fields [68–70]. This was unsurprising given the fact that research in this field is a relatively recent.…”
Section: Discussionmentioning
confidence: 76%
“…Now there are more than 400 million people suffering from diabetes, and the number is predicted increased to 642 million by 2040. As patients must be faced with longtime drug administration, self-nursing, food restriction, and diabetic complications during the progression of diabetes, patients are more likely to experience depressive symptoms [33]. Worldwide, about half of diabetic patients have severe depression [34].…”
Section: Discussionmentioning
confidence: 99%